2010
DOI: 10.1063/1.3499654
|View full text |Cite
|
Sign up to set email alerts
|

1.54   μ m emitters based on erbium doped InGaN p-i-n junctions

Abstract: We present here on the growth, fabrication and electroluminescence ͑EL͒ characteristics of light emitting diodes ͑LEDs͒ based on Er-doped InGaN active layers. The p-in structures were grown using metal organic chemical vapor deposition and processed into 300ϫ 300 m 2 mesa devices. The LEDs exhibit strong emissions at 1.0 and 1.54 m, due to Er intra-4f transitions, under forward bias conditions. The emitted EL intensity increases with applied input current without exhibiting saturation up to 70 mA. The integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 19 publications
(23 reference statements)
1
34
0
Order By: Relevance
“…6(b). The red EL was observed even at the forward bias higher than 5 V. This situation is similar to the OMVPE grown LEDs [16,22]. Under such high forward bias, question arises, of whether the emission by the electron-hole injection is enabled, because the GaN:(Eu, Mg) active layer's high resistance and high electric field may apply in the active layer.…”
Section: Properties Of Gan:eu Ledsmentioning
confidence: 62%
See 1 more Smart Citation
“…6(b). The red EL was observed even at the forward bias higher than 5 V. This situation is similar to the OMVPE grown LEDs [16,22]. Under such high forward bias, question arises, of whether the emission by the electron-hole injection is enabled, because the GaN:(Eu, Mg) active layer's high resistance and high electric field may apply in the active layer.…”
Section: Properties Of Gan:eu Ledsmentioning
confidence: 62%
“…Although the EL intensity under the forward bias conditions was five to 10 times more intense than reverse bias condition, the excitation mechanism under forward bias was not fully understood. Dahal et al reported the electroluminescence from Er doped InGaN p-i-n structure under the forward bias condition [16]. However, their device required forward-bias of about 12.5 V to obtain 20 mA current injection.…”
Section: Introductionmentioning
confidence: 99%
“…RGB-color-integrated RE-doped GaN thin film electroluminescence (EL) devices, and light-emitting high electron-mobility transistors (HEMTs) with spatially selective Eu doping region have been fabricated [10,11]. Light-emitting diodes (LEDs) with Eu doped GaN (GaN:Eu) and Er doped InGaN active layers showing red and infrared emission have been demonstrated [12][13][14]. For further development of device performance, a fundamental technology for optically activating RE ions in a crystal is required.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Recently, red and infrared emissions from light-emitting diodes (LEDs) with Eu-doped GaN (GaN:Eu) and Er-doped InGaN active layers have been realized under current injection. 12,13 Several emission peaks have been observed in GaN:Eu around 620 nm corresponding to the 5 D 0 -7 F 2 transition, which suggests the existence of several different optical sites. [14][15][16][17][18][19][20] At least nine different optical sites revealed by combined excitation-emission spectroscopy (CEES) by Fleischman et al 15 The luminous efficiency and excitation efficiency strongly depend on the optical site and not all the Eu ions contribute to the luminescence.…”
Section: Introductionmentioning
confidence: 99%